John L. Brown’s Epistolary Wit - Raphaël Ricaud (Angles)
John Lackey Brown was a literary correspondent in Paris in the aftermath of World War II. He was later posted as cultural attaché in Brussels, Rome and Mexico City during the first two decades of the Cold War. Those who knew him best say he was appreciated for his good humor, wit and love of culture. He is even said to have set the standard for the profession. Verba volant, scripta manent (spoken words fly away, written ones remain). Due to the ephemeral and private nature of asides, one can only speculate on this Cultural Affairs officer’s use of wit and its efficacy. However, there is a host of archival material at the Lauinger Library (Georgetown University) which can be mined for answers. Based on a sample of these letters, this paper sets out to classify and analyze the use of wit Brown made in his varied correspondence, and to study the extent to which it served a diplomatic purpose. In the end, I show wit was not an addition to Dr. Brown’s diplomatic endeavor; it was an integral part of it. Quips were tension relievers, strengthening trans-national bonds that united him to his peers. But they were also a way to word what could not otherwise be said. John Lackey Brown was not the epitome of the cultural attaché because he used wit and diplomacy. He stood out because he used wit as diplomacy.